Deteksi Kerusakan Jalan Menggunakan Vision Transformer Berbasis Citra Digital - Melsa Sentia Asta; Jumigih Andrian; Dhemes Ichsan Ramadhani; Perani Rosyani (CV. Shofanah Media Berkah, 2025)
Road damage, such as potholes and cracks, is an infrastructure problem that can increase the risk of accidents and reduce road user comfort. Conventional road inspection methods are still manual, subjective, and inefficient. This study aims to implement and deploy Vision Transformer (ViT) as an automatic image-based road damage classification method. The dataset used consists of 5,444 road condition images divided into three classes: no damage, potholes, and cracks, with an unbalanced data distribution. All images were preprocessed, consisting of a uniform size of 128x128 pixels and pixel value normalization. A lightweight version of the Vision Transformer model was built and tested using Google Colab, despite limited computing resources. Test results show that the model achieved an accuracy of ±89.7%, with the best performance in the no damage and pothole classes. However, performance in the crack class was still relatively low due to the limited data volume and the small visual characteristics of cracks. The results indicate that Vision Transformer has good potential as an automated solution for monitoring road conditions, although further development is needed to improve performance in minority classes.